Bell's palsy during rechallenge of immune checkpoint inhibitor. Issue 2 (16th January 2023) - Takemura, Kohji; Yamanaka, Taro; Hayashida, Michikata; Kizawa, Rika; Yamaguchi, Takeshi; Tanabe, Yuko; Sakaguchi, Kazushige; Suyama, Koichi; Urakami, Shinji; Miura, Yuji
Abstract : Introduction: The peripheral nervous system is one of the target organs of immune‐related adverse events. Peripheral facial nerve palsy, also called Bell's palsy, which is induced by immune checkpoint inhibitors, is quite rare, and its clinical features are not well known. Case presentation: A man with renal cell carcinoma who received rechallenging immune checkpoint inhibitor therapy developed unilateral facial palsy and was diagnosed with Bell's palsy. He did not have any severe immune‐related adverse events during his previous immune checkpoint inhibitor treatment. Corticosteroid therapy was immediately initiated, and his facial palsy symptoms promptly improved. Conclusion: Physicians should be aware that Bell's palsy can occur as an immune‐related adverse event. Additionally, careful observation is necessary during rechallenge with immune checkpoint inhibitors, even in patients who did not have previous immune‐related adverse events.